The larva and the food plant of Dirphia sombrero Le Cerf, 1934 (Lepidoptera: Saturnidae, Hemileucinae) - Vitor O. Becker; Almir C. Almeida (SHILAP)
The last instar larva of Diphia sombrero Le Cerf, 1934, an endemic species to the southern Brazil Atlantic Forest, is described and illustrated, and its food plant is recorded.